The Relationship Between Family Support And Anxiety Levels In Children Aged 5–18 Years With Chronic Kidney Disease At Haji Adam Malik Hospital Medan - Damanik, Rani Kawati; Sipayung, Rosetty Rita; Purba, Sri Dearmaita; Rejeki, Rika (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Anxiety is a problem characterized by refusing to be given nursing care, sleep disturbances, restlessness, worry, fear, crying easily, decreased appetite. The presence of family support can reduce the patient's anxiety level and influence the level of support they receive. The aim of this research is to identify the relationship between family support and the anxiety level of children suffering from chronic kidney failure aged 5-18 years at Haji Adam Malik Hospital. This type of research is correlation analysis with a Cross Sectional approach. The population in this study were families and children with GGK, the sample in this study was 73 people using a total sampling technique. The tool used to measure family support and the anxiety level of children with chronic kidney failure aged 5-18 years is a questionnaire. From the data, 18 people (24.7%) had good family support with anxiety in children, 10 people (13.7%) in the non-anxious category, 6 people in the mild anxiety category (8.2%), 2 people in the moderate anxiety category (2.7%). Of the 37 people (50.7%) who have sufficient family support, 5 people (6.8%) are not anxious in the child's anxiety category, 22 people are in the mild anxiety category (30.1%), 10 people are in the moderate anxiety category (13.7%). Of the 18 people (24.7%) who had less family support with anxiety in children in the non-anxious category, 3 people (4.1%), in the mild anxiety category, 5 people. It was concluded that there was a relationship between family support and the level of anxiety in children with CKD aged 5-18 years at Haji Adam Malik Hospital (p value = 0.005). It is hoped that the suggestions in this study can increase family support in reducing anxiety in children by providing religious education to children, always accompanying children in the treatment of chronic kidney failure. Keywords: Family Support, Anxiety for CKD Children